Geographic Information System Pencarian Rumah Relokasi Dampak Erupsi Gunung Sinabung dengan Metode Formula Haversine - Surya Aprianta Sinuraya (Journal of Computing and Informatics Research, 2022)
The eruption of Mount Merapi Sinabung from 2010 to the present, resulted in a large number of residents who had to be evacuated because they could not contain a place, so it had to be relocated in order to neutralize the number of refugees. Where the relocation is carried out in various places both in rural areas and in buildings in the area around Karo district. However, with this relocation, many people, both relatives and families as well as a number of institutions wishing to provide extension assistance, find it difficult because of the lack of information about the location and distance that must be traveled in order to get to the relocation site. Based on these problems, the author will discuss the creation of a Geographic information system for finding relocation sites by applying the Haversine formula method. In order to be able to determine the distance to the relocation site so that later it can help the community in finding a relocation place